The future of workplace wellness programs. Issue 1 (13th February 2017) - Ho, Sam
Abstract : Purpose: A comprehensive look at how technology, health plan design and employee communication can improve workplace wellness programs. Design/methodology/approach: There are numerous ways for employers to enhance their workplace wellness programs, helping to improve employee health and more effectively manage health-care costs. Findings: There are numerous ways for employers to enhance their workplace wellness programs, helping to improve employee health and more effectively manage health-care costs. Originality/value: The paper is original to Strategic HR Review .